Born to be a cowboy - Ryan, R. C., 1937-; Pine, A. J. (Ryan, R. C., 1937- Montana strong novel., 2019)
After running wild in his youth, Finn Monroe is now on the other side of the law as the local attorney. Between his practice and working at his family's ranch, his days aren't as exciting as they used to be--until Jessica Blair steps into his office. Gorgeous and determined, Jessie has a hunch her aunt is in trouble, and Finn is her last hope. As someone who relies on facts rather than feelings, Finn is skeptical. But it can't hurt to do a little digging. Jessie knows her aunt, and there is no way she would disappear on an "extended honeymoon" after hastily marrying a smooth-talking cowboy. Something is wrong, and Jessie is going to find out what. As soon as she and Finn start poking around, it becomes clear someone is willing to go to great lengths to keep them from the truth. But as the danger grows, so does their attraction. With both their lives on the line, Finn will discover just how far he'll go to keep Jessie safe.